2016
DOI: 10.1007/s13239-016-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

On-X Heart Valve Prosthesis: Numerical Simulation of Hemodynamic Performance in Accelerating Systole

Abstract: Numerical simulation of the bileaflet mechanical heart valves (BMHVs) has been of interest for many researchers due to its capability of predicting hemodynamic performance. A lot of studies have tried to simulate this three-dimensional complex flow in order to analyze the effect of different valve designs on the blood flow pattern. However, simplified models and prescribed motion for the leaflets were utilized. In this paper, transient complex blood flow in the location of ascending aorta has been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…This research utilized the 23-mm On-X heart valve. The model was generated using SolidWorks software, with structural information obtained from Mirkhani et al [ 18 ]. The simulation domain consisted of four components: the front aortic section, the MHV, the Valsalva sinus, and the back aortic section, as illustrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This research utilized the 23-mm On-X heart valve. The model was generated using SolidWorks software, with structural information obtained from Mirkhani et al [ 18 ]. The simulation domain consisted of four components: the front aortic section, the MHV, the Valsalva sinus, and the back aortic section, as illustrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The fabrication of Bileaflet Mechanical Mitral Heart Valve was carried out using graphite with 1.95g/cm 3 density because of its reported hemocompatibility and antithrombotic behavior in biomedical applications. 18 the 5-axis CNC machine was used for the fabrication of bileaflet mechanical heart valve whereas the PyC coating was done by the CVD technique. The main parts of the prototype were two leaflets and external orifice after machining and finishing of final parts leaflets were assembled into the butterfly, shaped hinges engraved in orifice.…”
Section: Figure 1: Commercially Available Heart Valve Models Materials and Methodsmentioning
confidence: 99%
“…Other researchers proposed a bionic double-leaf mechanical heart valve. The results showed that the bionic valve produced a smaller pressure gradient of the valve and reduced the generation of turbulence (Mirkhani et al, 2016). The application of the valve leads to better hemodynamic performance.…”
Section: Introductionmentioning
confidence: 99%